WHAT BRINGS PROFESSIONAL (DIS)SATISFACTION IN DENTISTRY: A SELF-ASSESSMENT OF WORK ENVIRONMENTAL FACTORS АND ORGANIZATIONAL COMMUNICATION - Nadya Avramova (Peytchinski Publishing, 2023)
Purpose: To investigate the influence of self-assessed working environment factors and organizational communication on professional satisfaction among dentists in Bulgaria. Material/Methods: A self-administered anonymous questionnaire consisting of 37 items about socio-demographic characteristics, motivation, work environment and economic factors was mailed to a group of 1427 dentists from 107 cities and villages in Bulgaria. Job satisfaction was assessed by using a three-point scale - satisfied, partly and dissatisfied. To search for significant associations statistical package, IBM SPSS Statistics 25.0 was used. The significance level was set at p<0.05. Results: A total of 436 dentists provided duly completed questionnaires (response rate=30.5%). Type of clinical patient-centered activities, availability of dental assistants, working conditions (dental equipment and supplies), and non-clinical activities (sanitary and hygienic duties, document workflow, dental practice management, financial planning, etc.) were significantly associated with job satisfaction (p<0.05). Working hours, proper planning of the working schedule, and dentist-patient interactions were not found to be related to levels of professional satisfaction (p≥0.05). Conclusions: Dentists working under unsatisfactory conditions, without a dental assistant employed, those working only in their specialty and performing sanitary-hygienic and administrative activities, were most likely to be dissatisfied with their jobs.